How Kids View Cops: The Nature of Juvenile Attitudes Toward the Police Revisited - Hurst, Y. Gail (Race and social problems, 2023)
Research suggests that juveniles are generally less positive in their attitudes toward the police than are adults. The current study re-examines juvenile perceptions of and experiences with the police following one city’s attempt to improve the police-community relationship. Using data collected from 842 ninth through twelfth grade public high school students, bivariate and multivariate analyses are used to assess the attitudes of juveniles toward the police and the factors that are determinants of these attitudes. While attitudes toward police performance of specific job functions improved after the city initiative, general attitudes toward the police were worse. Race and contact with the police remained consistent determinants of less positive attitudes. Attitudes of juveniles toward the police were found to be unfavorable across a number of dimensions and have actually decreased compared to findings in the same jurisdiction 15 years earlier. This is troubling for several reasons. First, the finding supports claims of prior research on juvenile perceptions of injustice during encounters with police. Second, attitude measures associated with distributive and procedural justice were not positive suggesting that juvenile compliance and cooperation with the police may not be forthcoming. Third, attitudes of youth are likely to persist for some time because of intergenerational transmission of these perceptions.